Aryl Methyl Sulfone Construction from Eco‐Friendly Inorganic Sulfur Dioxide and Methyl Reagents. Issue 13 (12th February 2019) - Wang, Ming; Zhao, Jiaoyan; Jiang, Xuefeng
Abstract: A three‐component cross‐coupling protocol of boronic acid, sodium metabisulfite, and dimethyl carbonate was developed for the construction of significant functional methyl sulfones, in which introduction of sulfur dioxide at the last stage was successfully achieved in one step. Inorganic sodium metabisulfite was used as an eco‐friendly sulfur dioxide source. Green dimethyl carbonate was employed as methyl reagent in this transformation. Diverse functional methyl sulfones were obtained from various readily available boronic acids. Notably, the last‐stage modification of pharmaceuticals and the synthesis of Firocoxib were efficiently established through this strategy. Abstract : Expanding the library : A three‐component cross‐coupling reaction of boronic acid, sodium metabisulfite, and dimethyl carbonate is efficiently established for the construction of an aryl methyl sulfone library. Pharmaceutical synthesis and late‐stage diversification are afforded through this protocol.